2021
DOI: 10.34010/icobest.v2i.294
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioural Theory Relevance of Mental Accounting for the Investment Decisions

Abstract: At first, investors in investing not only used estimates of investment instruments, but psychological factors had also determined the investment. In fact, various parties state that the psychological factor of this investor has the biggest role in investing. This study is an experiment on financial option pricing. Arbitrage-free option pricing is tested against three hypotheses based on mental accounting. The purpose of this study is to identify and confirm the theory of mental accounting on informed decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Mental Accounting is when someone makes a decision, they always mentally consider the advantages and disadvantages (Hamzah, 2022). Investors who use mental accounting when making transaction decisions always consider the costs and benefits of these decisions, so they feel safe (Nusa, 2021;Sukamulja et al, 2019). Someone with a high accounting mentality will be more courageous in making a decision, and someone with a low accounting mentality will be less courageous in making decisions (Hamzah, 2022).…”
Section: Mental Accountingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental Accounting is when someone makes a decision, they always mentally consider the advantages and disadvantages (Hamzah, 2022). Investors who use mental accounting when making transaction decisions always consider the costs and benefits of these decisions, so they feel safe (Nusa, 2021;Sukamulja et al, 2019). Someone with a high accounting mentality will be more courageous in making a decision, and someone with a low accounting mentality will be less courageous in making decisions (Hamzah, 2022).…”
Section: Mental Accountingmentioning
confidence: 99%
“…Therefore, it can be concluded that mental accounting has a significant positive impact on student investment decisions at FEB UNRAM, and H3 is accepted. According to Hamzah (2022), Nusa (2021), andSanti et al (2019), this research is backed by evidence showing that Mental Accounting strongly influences investing decisions. Mental Accounting can be defined as the application of an individual's cautious mindset when making financial choices.…”
Section: The Effect Of Mental Accounting On Investment Decisionsmentioning
confidence: 99%